Incidence and Predictors of Flares in the Postpartum Year Among Women With Inflammatory Bowel Disease. Issue 12 (2nd January 2020) - Yu, Amy; Friedman, Sonia; Ananthakrishnan, Ashwin N
Abstract: Background: The postpartum period is marked by physiological and psychological stresses that may impact activity in inflammatory bowel disease. The predictors and outcomes of disease activity during this period have not been well characterized. Methods: We performed a retrospective review of inflammatory bowel disease patients who underwent successful pregnancy and live birth at 2 referral institutions. Data on patient and disease factors including disease activity before and during pregnancy were abstracted from the medical records. We noted whether therapy was dose-reduced or stopped during pregnancy at each trimester and after delivery. Multivariable logistic regression of independent predictors of postpartum flare was performed, adjusting for relevant covariates. Results: We identified a total of 206 eligible women (mean age, 33.2 years). Of these, 97 (47%) had a diagnosis of Crohn's disease, whereas the remainder had ulcerative colitis. Nearly half the women delivered vaginally (53%), and the rest delivered by Caesarean section (47%). In the entire cohort, 65 (31.6%) experienced a postpartum flare within the year after delivery. In multivariable analysis, development of a postpartum flare was predicted by disease activity during the third trimester (odds ratio [OR], 6.27; 95% confidence interval [CI], 2.81–17.27), therapy de-escalation during pregnancy (OR, 3.00; 95% CI, 1.03–8.68), and therapy de-escalation after pregnancy (OR, 4.43; 95% CI, 1.55–12.65). Postpartum disease flare was not related to disease type, duration of disease, or mode of childbirth. Conclusions: One-third of women with inflammatory bowel disease may experience disease flare during the postpartum year. Continued optimization of therapy before, during, and after pregnancy is essential to prevent this morbidity.